2019
DOI: 10.1177/2036361318820171
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue leiomyosarcoma—diagnostics, management, and prognosis: Data of the registry cancer of the center of Tunisia

Abstract: Background:Soft tissue leiomyosarcomas are rare, accounting for almost 5%–10% of all soft tissue sarcomas; they account for almost 1% of all sarcomas. They are aggressive tumors where location, size, and management require a multidisciplinary approach. Since there are few series published, we here analyze epidemiological pattern, clinical and pathologic features of soft tissue leiomyosarcomas.Methods:We conducted a retrospective study of 29 consecutive cases of histologically proven soft tissue leiomyosarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…PLB was first described by Evans and Sanerkin 11 and Overgaard et al, 12 who each identified an immunohistochemical profile of cytoplasmic myofilaments and dense bodies with various basal lamina fragments. Notably, this molecular pattern was similar to SLMS, which is more common than PLB and accounts for nearly 5–10% of adult soft tissue sarcoma 13 . Though given the rarity of PLB, there are few small series in which the natural disease course is described.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…PLB was first described by Evans and Sanerkin 11 and Overgaard et al, 12 who each identified an immunohistochemical profile of cytoplasmic myofilaments and dense bodies with various basal lamina fragments. Notably, this molecular pattern was similar to SLMS, which is more common than PLB and accounts for nearly 5–10% of adult soft tissue sarcoma 13 . Though given the rarity of PLB, there are few small series in which the natural disease course is described.…”
Section: Discussionmentioning
confidence: 59%
“…Few recent studies have demonstrated a survival benefit with surgery and adjuvant therapy in SLMS. Mestiri et al published the results of 29 consecutive cases of histologically proven SLMS, and in addition to high rates of local recurrence (55%) and initial metastases, they note the majority of patients (69%) underwent surgery, and they suggest surgery appears to be the cornerstone of treatment for SLMS 13 . More recently, Qian et al 4 found surgery and chemotherapy together improved survival in patients with SLMS and metastases at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The clinical course of patients with LMS is often hard to predict as LMS is a highly aggressive tumor with propensity to metastasize. 2,5 Previous studies have used conventional univariate or multivariate statistical analyses to assess the magnitude of association a single variable has with an outcome such as overall survival. 24,28,29 To the best of our knowledge, this is the first study of its kind to use machine learning to assess prognosis of patients with trunk or extremity LMS.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma (LMS) is a common subtype of soft tissue sarcoma (STS) arising from smooth muscle cells and accounting for 10−20% of all STS 1–3 . A heterogeneous and complex tumor, LMS encompasses various cytogenetic and molecular abnormalities 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite advancements in diagnostic and therapeutic strategies, the prognosis for leiomyosarcoma remains poor. The five-year survival rate ranges from 20% to 50% depending on the extent of the disease and the location of the tumor [ 3 ].…”
Section: Introductionmentioning
confidence: 99%